Peculiarities of seed germination and seedling growth of Scots pine trees with different root rot resistance - Ustskiy, I. M.; Dyshko, V. A.; Mykhailichenko, O. A. (Forestry and Forest Melioration, 2019)
Introduction A number of researchers recommended orientating towards natural regeneration in pine stands affected by annosum root rot. They believed that viable undergrowth of pine on a pathological background could be the result of induced resistance. We have not found any reproductive features of trees with different resistance to root rot. Most of the works have analysed Scots pine seedlings of different geographical or ecological origin. The aim of our study was to find out peculiarities of seed germination and the growth of Scots pine seedlings with a different health condition in the root rot foci. Materials and Methods Seeds for the research were collected in pure V-age-class pine stand affected by root rot in the Derhachivske Forestry of Kharkiv Forest Research Station. We selected 21 model trees with similar mensuration indicators but with different health conditions by their external features and position in the root rot foci. In the dieback foci, we selected trees as without external signs of the disease (resistant), so with them (affected). Outside of the dieback foci, there were trees without external signs of weakening (control). The study of the pine reproductive material was carried out by means of standard methods in the laboratory. The main qualitative indicators of seeds (quality class, germination energy, laboratory germination, and soil germination) and seedlings (growth intensity, length, and the ratio of underground and aboveground parts of seedlings to total length) were determined. The effects of disinfection agents (H2O2 and KMnO4) and various soil conditions (sand; sand-soil mixture) on the biometric characteristics of seedlings and soil germination of seeds were investigated. Results As resistant trees do not grow in all dieback foci, we believe that most of the young growth is the offspring of the affected or healthy trees growing outside them. Seeds of resistant trees had better germination energy (75.0%), laboratory (87.0%) and soil (74.9%) germination capacity than those of the affected ones (70%, 79.1%, 73.3%, respectively). However, they had a worse seedling growth rate at the beginning of their ontogeny compared to the affected ones. The seeds of resistant trees had the better average quality class (1.9) than those of the affected trees (2.4) and of control (2.0). The difference between the average sizes of seedlings of resistant and affected trees was not significant (up to 5%). The proportions of root length (26.5%) and aboveground part covered with needles (18.7%) of the seedlings of resistant trees were larger than those of the affected ones (22.4 and 16.4%, respectively) and were not less than the control ones (21.2). No significant benefits from the use of various disinfectants or soil conditions were identified. For certain reasons, the reproductive material of resistant trees is characterized by a greater variation of indicators (Cv = 12.5–34.7%) than those of affected trees (Cv =10.3–26.5%). Conclusions The role of resistant trees in reforestation of the gaps is insignificant since they do not grow in all dieback foci. Most undergrowth in the dieback foci is the offspring of affected or healthy trees outside of them. At the beginning of ontogeny, the growth rate of the seedlings of resistant trees is less than that of the affected and control ones. The advantages of the reproductive material of trees with high resistance confirm the need to use such trees to create a forest seed orchard in order to be able to afforest the areas where the disease foci may occur. 2 Figs., 3 Tables, 23 Refs.